Mixed capital of Islamic financial institutions, is it Islamic? - Abdul Rahman, Zaharuddin (Red Money, 2011)
Among the most debated issue concerns the initial capital of Islamic banks and takaful companies, especially when initiated by a conventional parent company. Some people doubt the purity of the capital in Islamic banks and takaful and eventually deny the benefits of Islamic banking. Hence, the question here is could Islamic banks and takaful be truly Islamic when its capital is not completely halal?